A Study on solid waste management at Kg.Jelempok, Arau - Shazryenna Dalang (Penerbit Universiti Malaysia Perlis, 2011)
Solid waste management has six main functional elements. There are Waste Generation, Storage, Collection, Transportation, Recycle and Process and Disposal. Problem can occur in any stage of the management. In Malaysia, there are many efforts have been done to increase the quality of solid waste management in order to create a not only clean, but with good quality environment. However, all the efforts are focusing at urban areas. The solid management waste in rural area still requires more technologies, facilities and practices. Thus, the study has been done at a rural area located in the smallest state of Malaysia; Kg.Jelempok, Perlis. There are three method of solid waste management applied at Kg.Jelempok. 54% of 50 respondents dispose their waste by illegal combustion, 16% send their waste to the nearest collection site, which located at Arau and Kodiang. The remaining 30% manage their waste by both methods. The water quality has been tested at three different points, and some parameters tested are not complying the Interim National Water Quality Standard for Malaysia. Other than that, the leachate sample also had been analysed. Some parameters are not complying the 3rd Schedule of the Environmental Quality Act 1974; Environmental Quality (Sewage and Industrial Effluent) Regulation 1979 Standard. Thus, there are some better solution has been suggested throughout this study for the residents of Kg.Jelempok and for the related local authorities. This study will help rural area residents to have healthy life style and environment to live in.